Hepatoprotective and Cytotoxic Activities of Capparis cartilaginea Leaves Extract - Al-Qubati, Sameha Abdullah Abdul-gabbar Ahmed (My University, 2025)
Capparis cartilaginea leaves extract (CCLE) has potential therapeutical uses as a protective and ameliorated agent against different diseases. However, nothing has yet been reported on its hepatoprotective effect against anti-tuberculosis drugs (ATD) induced liver injury. This study aimed to detect this effect through a hepatoprotective study to investigate CCLE protective activity against Isoniazid/Rifampicin INH/RIF hepatotoxicity and by a cytotoxicity study to evaluate its in-vitro cytotoxic effect against the human hepatocellular carcinoma (HepG-2) cell line. The hepatoprotective study designed by grouping thirty male albino rats (150±20)g randomly into five groups (6 rats/group) as follows: Group1: Normal group received only distilled water orally for 21 days, Group 2: hepatotoxic non-treated HTNT group received INH/RIF daily dose (100mg/kg each) orally for 21 days, Group3: HT/SM group received 100mg/kg silymarin 2 hours before INH/RIF (100mg/kg each) daily dose for 21 days, Groups 4,5 (HT/CCLE100,200) were CCLE treated groups received 100mg/kg ,200mg/kg of CCLE 2 hours before INH/RIF (100mg/kg each) daily dose for 21 days. Cytotoxicity study was achieved by MTT analysis. Results showed that CCLE significantly reduced ALT in 100mg/kg ,200mg/kg treated groups to levels close to that in normal. In addition, 100mg/kg CCLE improved lipid profile by reducing cholesterol level than that in HTNT group. The histological examinations in this study supported the biochemical results describing both INH/RIF hepatotoxicity and the potential hepatoprotective effects of silymarin and CCLE. Cytotoxicity study results revealed that CCLE had a weak cytotoxic activity against the HepG2 cell line with an IC50 value of 167.81±6.23 μg/ml. Finaly it is clear that results of this study explore that C. cartilaginea leaves extract had a significant hepatoprotective activity against the hepatotoxicity induced by anti-tuberculosis drugs.
Keywords: Hepatoprotective Activity; Cytotoxic Activity; Capparis cartilaginea; Pharmacology; Pharmaceutical Sciences; Sana'a